A Review on MoS2 Properties, Synthesis, Sensing Applications and Challenges - Samy, Omnia; Zeng, Shuwen; Birowosuto, Muhammad Danang; El Moutaouakil, Amine (Crystals (Basel), 2021)
Molybdenum disulfide (MoS2) is one of the compounds discussed nowadays due to its outstanding properties that allowed its usage in different applications. Its band gap and its distinctive structure make it a promising material to substitute graphene and other semiconductor devices. It has different applications in electronics especially sensors like optical sensors, biosensors, electrochemical biosensors that play an important role in the detection of various diseases’ like cancer and Alzheimer. It has a wide range of energy applications in batteries, solar cells, microwave, and Terahertz applications. It is a promising material on a nanoscale level, with favorable characteristics in spintronics and magnetoresistance. In this review, we will discuss MoS2 properties, structure and synthesis techniques with a focus on its applications and future challenges.